Current Population Survey: Voter Supplement File, November 1998 ([Verlag nicht ermittelbar], 1999)
This survey provides data on labor force activity for the week prior to the survey. Comprehensive data are available on the employment status, occupation, and industry of persons 15 years and over. Personal characteristics such as age, sex, race, marital status, veteran status, household relationship, educational background, and Hispanic origin are also provided. Questions unique to this supplement pertain to citizenship, voting status, and registration status and were asked of household members who were United States citizens and 18 years of age and older.